(untitled) (Journal of the College of Education for Women, 2019)
Current search aims to identify the creative thinking of the kindergarten teachers andsolving professional problems among kindergarten teachers skills, and whether the level ofcreative thinking in solving professional problems, according on marital status years ofservice academic achievement of teachers as well as to identify the correlation between thetwo variables the current sample consisted of (300) teachers to achieve the objectives of thestndy , the researcher used two measures, one to measure creative thinking and the other tomeasure the solution to the problems of professional kindergarten teachers skills. It has beenshown. validity and reliability of the two measures. The present stndy aims to identify .1. Some kindergarten teachers and (80%) them hare of creative thinking2. .Both professional (years of service) gives a kindergarten teacher good skills in creativethinking, becamse the accumulation of experiences.3. . There is a positive correlation which statistically significant, The more creative thinkingskills for kindergarten teachers, the more they became to have a high potential in solvingprofessional problems.The researcher arrired a number of recommendations and suggestions.